If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4m + -9 = 11 Reorder the terms: -9 + 4m = 11 Solving -9 + 4m = 11 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + 4m = 11 + 9 Combine like terms: -9 + 9 = 0 0 + 4m = 11 + 9 4m = 11 + 9 Combine like terms: 11 + 9 = 20 4m = 20 Divide each side by '4'. m = 5 Simplifying m = 5
| 9x-4=4x+27 | | 2(-5x-7)=16 | | 2[-(2+13)+11]=2(x+2) | | -7(2x-3)=28 | | .6-0.25f=f-3 | | 4ln(x)-ln(x^4)= | | Y=.5(3)+1 | | 2x-3x+x+9x=2-4+35 | | 2x^3+2x^2-72=0 | | -10(p+8)=110 | | -27+v=-12 | | -5-5x+6x=6 | | 5e^6+7=12 | | -2.7x+4(x-1)=10.5(2x+6)+31.5 | | -(5a+5)-3(a-6)= | | 48+6x=90 | | 5e^1+7=12 | | 9x+1=3x-13 | | 2x+6.8+8x+1.4+x=90 | | 3s^2-26s-9= | | 8p+7=13+7p | | -2(1-4x)=6x+12 | | 7(7x-1)-18=47x+7 | | 8b=2b | | 64c^2-16=0 | | 5(2x-4)=0 | | -8(x+3)+2x+5=7x+9 | | 3+x+27=180 | | (2x+3)(4x-4)= | | [9(p+4)-18]-[2(p-4)+1]= | | 9(2k+3)+2=11(k-.5) | | .4x+7=.6x |